2015
DOI: 10.1063/1.4927601
|View full text |Cite
|
Sign up to set email alerts
|

Impact of lateral carrier confinement on electro-optical tuning properties of polariton condensates

Abstract: Tunnel-assisted manipulation of intersubband polaritons in asymmetric coupled quantum wells Appl. Phys. Lett. 89, 171109 (2006); 10.1063/1.2367664Enhancement of the quantum-confined stark effect utilizing asymmetric quantum well structures Appl.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…Since the QWs are located in the intrinsic region, moderate applied voltages of a few hundred mV should suffice to shift the QW exciton emission up to several meV. It is interesting to note that, while the QCSE has been studied for excitonpolaritons in the linear regime [82][83][84], certain peculiarities related to phonon enhanced tunneling effects between nearby QWs and carrier screening were observed recently [85,86]. Under specific circumstances, in particular if diffusion of the reservoir is restricted, these effects indeed lead to a blueshift of the polariton resonance in the presence of the electric field, which may present a complication for the realization of electrostatic polariton traps.…”
Section: Electrostatic Trapsmentioning
confidence: 99%
“…Since the QWs are located in the intrinsic region, moderate applied voltages of a few hundred mV should suffice to shift the QW exciton emission up to several meV. It is interesting to note that, while the QCSE has been studied for excitonpolaritons in the linear regime [82][83][84], certain peculiarities related to phonon enhanced tunneling effects between nearby QWs and carrier screening were observed recently [85,86]. Under specific circumstances, in particular if diffusion of the reservoir is restricted, these effects indeed lead to a blueshift of the polariton resonance in the presence of the electric field, which may present a complication for the realization of electrostatic polariton traps.…”
Section: Electrostatic Trapsmentioning
confidence: 99%
“…We attribute this behavior to the quantum confined Stark effect, , which induces a red shift in the emission spectrum of a QW caused by an external electric field. Due to the excitonic component of polaritons, these particles’ emission energy is also effected when applying an electrical field. , A power series measurement is performed to show that polariton lasing is still present at an applied reverse bias voltage of −5 V. Details can be found in Supporting Information section 3. Here we experimentally show the possibility to influence the condensation conditions of our sample and are therefore able to switch the lasing from the topological to a trivial mode, depending on the applied voltage.…”
Section: Resultsmentioning
confidence: 99%
“…As we know, an electric field has an important effect on the energy of excitons, specifically, it can reduce the overlap of electron and hole wavefunctions in quantum wells, which leads to the reduced vacuum Rabi splitting between excitons and photons. Recent experiments have shown the influence of an electric field on the energy of EPs [28,29]. Additionally, it is found that an external electric field can be used to directly control the spin of an EP condensate and emission polarization [30].…”
Section: Model and Formulation 21 A Possible Experimental Methodsmentioning
confidence: 99%